On screen and off : cinema and the making of Nazi Hamburg - Berg, Anne, 1977- (University of Pennsylvania Press, 2022)
The Nazi regime imagined film as a powerful tool to shape National Socialist subjects. Tracing discourses around film production and film consumption in the city of Hamburg, On Screen and Off illustrates how Nazi ideology was envisaged, imagined, experienced, and occasionally even fought over.